Production equipment and production method of hydroxyl chromium oxide - ZHOU QIANG; DAI YU; HU XIANGLONG (2014)
The invention discloses production equipment and a production method of hydroxyl chromium oxide. The production equipment comprises a steel belt type reducing furnace and a slurry-making device, wherein the slurry-making device comprises a mixing tank and a slurry pump; a material absorbing hole of the slurry pump extends inside the mixing tank; the production equipment further comprises a hydrolysis device arranged between the steel belt type reducing furnace and the slurry-making device, wherein the hydrolysis device comprises a first water tank with a water inlet, a first pressing roller arranged inside the first water tank and a connecting tube which is fixed on the outer wall of the first water tank and is capable of communicating the inside of the first water tank with the inside of the mixing tank; the steel belt enters the inner part of the first water tank after stretching out from a cooling section of the steel belt furnace type reducing furnace and extends out of the first water tank after penetrat